2012
DOI: 10.1002/cncy.21219
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal washing cytologic analysis of ovarian serous tumors of low malignant potential to detect peritoneal implants and predict clinical outcome

Abstract: Background Patients with ovarian serous tumors of low malignant potential (OSLMP) who have peritoneal implants, especially invasive implants, are at increased risk of developing tumor recurrence. The ability of peritoneal washing (PW) cytology, to detect the presence and type of peritoneal implants has not been adequately investigated, and its prognostic significance is unknown. Methods We retrospectively reviewed records and PW specimens of 101 patients diagnosed with and treated for OSLMP between 1996 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 14 publications
(24 reference statements)
0
29
0
Order By: Relevance
“…Peritoneal cytology is an integral part of staging surgery in ovarian cancer (Sneige et al 2012). Five patients had positive peritoneal cytology in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Peritoneal cytology is an integral part of staging surgery in ovarian cancer (Sneige et al 2012). Five patients had positive peritoneal cytology in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…In addition one study showed that the presence of peritoneal implants in ovarian cancers with a low malignant potential demonstrated a high risk of recurrence (Sneige et al, 2012). In another DOI:http://dx.doi.org/10.7314/APJCP.2014.15.21.9405 Peritoneal Washing Cytology in Gynecologic Malignancies involvement (Ellen et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of peritoneal implants in ovarian cancers with a low malignant potential indicates a high risk of recurrence. PWC may be used to establish this risk (Sneige et al, 2012). In our study there was no patient with an ovarian cancer of low malignant potential.…”
Section: Discussionmentioning
confidence: 75%